Makroskopická perspektiva politické filosofie versus mikroskopická perspektiva empirie - Petr Krčál (AntropoWebzin, 2013)
The following article focuses on issuesof social justice. This text is divided into two mainparts. In the first one, I am concerned with thecharacteristic of the theory of social justice itselfand with the main theoretical approaches of thistheory – namely with egalitarianism, prioritarianismand (left) libertarianism. The second part isfocused on an analysis of the electoral programsof political parties which were elected into theCzech parliament in the elections of 2010. Themain point of this analysis is to locate and identifyproclamations about social justice which can berelated to theories of social justice. Through thisanalysis I want to demonstrate the possibility oftheories of social justice as a way of explaining thepolitical actions and the relation of political representationto social marginality.